MILP model for integrated line balancing and model sequencing problems for Mixed-Model Two-Sided Assembly Line - Mohd. Azmi, Nur Intan Liyana (Penerbit UTM Press, 2017)
This research explores two interrelated problems in Mixed-Model Two-Sided Assembly Line (MMTSAL), which are line balancing and model sequencing. These two problems are solved simultaneously using Mixed Integer Linear Programming (MILP) with the objectives of minimizing total utility work and idle time by considering various practical constraints. The problem is analyzed using small-size to large-sized test cases using General Algebraic Modelling System (GAMS) with the solver CPLEX. Experimental results indicate that integrating the problems help to minimize the proposed objective function. Also, it is found that the feasible solution for model sequence with the assignment of tasks to assembly line is optimal.